2020
DOI: 10.1056/nejmoa1917635
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib for Glucocorticoid-Refractory Acute Graft-versus-Host Disease

Abstract: BACKGROUNDAcute graft-versus-host disease (GVHD) remains a major limitation of allogeneic stemcell transplantation; not all patients have a response to standard glucocorticoid treatment. In a phase 2 trial, ruxolitinib, a selective Janus kinase (JAK1 and JAK2) inhibitor, showed potential efficacy in patients with glucocorticoid-refractory acute GVHD. METHODSWe conducted a multicenter, randomized, open-label, phase 3 trial comparing the efficacy and safety of oral ruxolitinib (10 mg twice daily) with the invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
460
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(519 citation statements)
references
References 30 publications
11
460
3
4
Order By: Relevance
“…Several different therapies have been used over the years with varying efficacy but none of these have been shown to be clearly superior. Ruxolitinib has recently been shown in randomized controlled trials to be more effective than "best available therapy" and is now seen as the primary choice for treatment of steroid refractory acute GVHD 9 . Other promising options are mesenchymal stem cells, especially in children, and photopheresis.…”
Section: Gvhdmentioning
confidence: 99%
“…Several different therapies have been used over the years with varying efficacy but none of these have been shown to be clearly superior. Ruxolitinib has recently been shown in randomized controlled trials to be more effective than "best available therapy" and is now seen as the primary choice for treatment of steroid refractory acute GVHD 9 . Other promising options are mesenchymal stem cells, especially in children, and photopheresis.…”
Section: Gvhdmentioning
confidence: 99%
“…JAK inhibition is one of the promising therapeutic strategies in the prevention and treatment of GvHD since pre-clinical animal studies with JAK inhibitors demonstrated a significant reduction of GvHD while maintaining or enhancing immune reconstitution compared to control groups [124,125,149,150]. Consistent with these pre-clinical studies, ruxolitinib was highly effective for steroid-refractory GvHD [151,152]. Similarly, the first prospective clinical trial with a JAK inhibitor, itacitinib (a selective JAK 1 inhibitor; ClinicalTrials.gov #NCT03139604), demonstrated encouraging efficacy in acute GvHD patients [153].…”
Section: Clinical Aspects Of Hdac Inhibitorsmentioning
confidence: 66%
“…Rux was superior in terms of ORR; however, there was no difference in cumulative incidence of 18-month NRM. 91 Infections and cytopenias remain limiting toxicities. The FDA has approved Rux for SR aGvHD.…”
Section: Cytokine Pathwaysmentioning
confidence: 99%